(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
This paper examines the increasing threats faced by environmental defenders in Indonesia, focusing on human rights violations in the context of ecological justice. Over the past few decades, Indonesia has experienced rapid industrialization, leading to widespread deforestation, environmental degradation, and conflicts over land use. As a result, indigenous communities and environmental activists have been at the forefront of resistance, fighting against exploitation of natural resources. However, these defenders often face harassment, intimidation, and violence from both state and non-state actors, particularly corporations involved in the palm oil, mining, and forestry sectors. This study analyzes key incidents of persecution, the legal frameworks intended to protect environmental defenders, and the challenges in implementing these protections. The research also highlights the roles of human rights organizations and international advocacy in raising awareness of these threats. By focusing on case studies from Kalimantan, Sumatra, and Papua, the paper underscores the importance of safeguarding environmental defenders’ rights to free speech, assembly, and protest. It concludes with policy recommendations for strengthening legal protections, improving law enforcement accountability, and promoting a rights-based approach to environmental justice.